KONSEP DAN IMPLEMENTASI SISTEM PENGENDALIAN MANAJEMEN DI ERA DIGITAL - Haryati, Risna (JURNAL PENDIDIKAN, HUMANIORA, LINGUISTIK DAN SOSIAL (JAGADDHITA), 2025)
The development of digital technology has transformed the way organizations design and implement management control systems (MCS). This article aims to examine the fundamental concepts of MCS and explore its implementation in the digital era through a literature review. The method used is a review of current academic and practical sources. The findings indicate that information technology, business process automation, and real-time data-based systems have enhanced the effectiveness of MCS, but they also pose new challenges such as data security and resistance to organizational cultural change. The article concludes with strategic recommendations for organizations seeking to develop adaptive MCS in the digital era.